ASSESSMENT OF SERUM C-REACTIVE PROTEIN/ALBUMIN RATIO AND RELATED FACTORS IN PLAQUE PSORIASIS (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the serum CAR and its association with demographic and clinical characteristics in patients with plaque psoriasis at Ho Chi Minh city Hospital of Dermato-Venereology.Methods: A cross-sectional study was conducted on 60 patients clinically and/or histologically diagnosed with plaque psoriasis. Additionally, 60 healthy individuals without psoriasis were included as a control group to compare CAR levels.Results: The value of CAR in psoriasis patients was 0.61 (range: 0.27-2.33), which was significantly higher than that of the control group at 0.23 (range: 0.12-0.54) (p < 0.001). Moreover, the CAR showed a statistically significant positive correlation with PASI score (r = 0.387, p = 0.002). Cardiovascular risk stratification based on hsCRP levels also revealed that psoriasis patients had significantly higher rates of moderate-to-high cardiovascular risk compared to controls.Conclusion: The serum CAR is elevated in patients with plaque psoriasis and is associated with both disease severity and increased cardiovascular risk.
Keywords: Psoriasis, CAR, cardiovascular risk.